A Descriptive Analysis for the Future of Journalism Studies in Emerging Artificial Intelligence (AI) and the Case of NewsGPT platform - Muzafalu Katamba; Bahar Kayıhan (Yeni Medya)
Technology has been applied in various activities almost in every field including journalism. There are visible changes in the way journalists do their professional work by the help of technology; the most important tool in the axis of these developments is artificial intelligence (AI). Today people can do news gathering and production, news reporting and news consumption among others on movable technological gadgets around the globe by the influence of AI. However, although technology can be seen as an opportunity when it comes to journalistic work, it has also been disadvantageous in some ways. Therefore, we need to rephrase journalism study programs to fit into the AI era to enable both AI and professional journalism to exist concurrently. In this line, this study has a through descriptive analysis aimed at explaining AI, NewsGPT platform and journalism, and how journalism studies should be re-modeled for the future to enable coming journalists know how to adopt with technology alongside professionalism. The study also adds knowledge to the discussion for the future possibilities of journalism studies. As a result of the study, it was revealed that the news on the NewsGPT platform has various problems such as bias and disinformation, and in this context, both algorithm journalism and journalism education should be rethought.